Adapting Prevention and Early Intervention Measures and Parenting Capacity Assessments in Neglect Cases Involving Parents with Intellectual Disabilities in South African Children's Court (African Disability Rights Yearbook, 2024)
The study explored how the South African social services and two Children’s Courts (Durban and Pietermaritzburg) meet their international and constitutional obligations in promoting access to justice for mothers with intellectual disabilities and their children. This archival study examined the court records of two Children’s Courts from 2010 to 2014. The review of child neglect cases found macro-level exclusions experienced by parents with intellectual and psycho-social disabilities, such as experience of heightened poverty, stereotypical ableist assumptions about parenting with a disability exhibited in social work reports, and few or non-existentsupports extended to parents to help them exercise their care responsibilities. Against the background of the findings from review of the court records and international law obligations on the South African state, this paper considers the role of the social worker in relation to offering and monitoring prevention and early intervention (PEI) services to families as one way to avoid more intrusive intervention in family life. The paper also considers adaptions to PEI measures and Parenting Capacity Assessments (where needed), and argues for specialist training to help social workers fulfil their role in supporting these parents. The role of presiding officers in actively monitoring the social workers’ provision of PEI as well as measures to enhance the meaningful participation of parents with intellectual disabilities in the court process are identified.